The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1177/0733464804265604
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Therapy Use Among the Young-Old (Ages 65 to 74): An Evaluation of the MIDUS Database

Abstract: By the year 2020, 20% of the U.S. population will be age 65 years or older. From a health care perspective, there is growing concern about the aging population. Little is known about the elderly and their use of alternative therapies. This study included data from the National Survey of Midlife Development in the United States (MIDUS). Three-hundred and thirty-five participants between the ages of 65 and 74 completed the interview and mailback questionnaire. Onehundred and forty-five individuals (43.3%) report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
(32 reference statements)
1
33
0
Order By: Relevance
“…In studies carried out on elderly about CAM usage, CAM usage rates vary between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . Because different CAM methods have been investigated in studies, different results on the frequency of CAM usage might have been obtained.…”
Section: The Frequency Of Cam Usagementioning
confidence: 99%
See 1 more Smart Citation
“…In studies carried out on elderly about CAM usage, CAM usage rates vary between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . Because different CAM methods have been investigated in studies, different results on the frequency of CAM usage might have been obtained.…”
Section: The Frequency Of Cam Usagementioning
confidence: 99%
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…Other important components of health self-management include financial resources, culture, and selfempowerment [7,8]. Current data suggest that most patients use CAM in addition to conventional medical treatments [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…To be precise, elderly are always willing to search ways which improve their health and found to use complementary and alternative medicine (CAM) more often than other age groups. 2,3 A study conducted in Australia showed that 60e80% of elderly consumers have declared use of at least one herbal or nutritional medicine on a regular basis. 2 According to National Center for Complementary and Alternative Medicine (NCCAM), complementary and alternative medicine (CAM) is defined as a group of diverse medical and healthcare systems, practices, and products that are not generally considered part of conventional medicine.…”
Section: Introductionmentioning
confidence: 99%